Pelaksanaan Layanan Konseling Komunitas Khusus bagi Warga Binaan di Rumah Tahanan - Nur, Edil Wijaya; Agung Setiawan; Andi Firdawati (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2024)
This article explores the necessity for specific community counseling services for inmates in correctional facilities, not only as corrective measures but also as support in rebuilding self-confidence, managing stress, and aiding in the rehabilitation process. Despite the acknowledged importance of counseling services, their implementation hasn't been well-structured within correctional facilities. The article depicts the execution of specialized community counseling services for inmates in a correctional facility in South Sulawesi, describing the methods, obstacles, and outcomes. A qualitative approach adopting descriptive methods was utilized to elucidate service implementation. Data collection involved interviews, observations, and document studies. The analysis revealed a primary focus on career development within these services, while personal, social, and educational aspects didn’t receive optimal attention. Major challenges included the complexity of individual issues, low participation in group counseling, and resource limitations. Balancing the emphasis on career development with comprehensive attention to individual needs is crucial for ensuring successful social reintegration. Comprehensive reviews and continuous evaluations are essential for improving services in the future.